Cerebral Venous Thrombosis in Paroxysmal Nocturnal Hemoglobinuria: A Series of 15 Cases and Review of the Literature - Meppiel, Elodie (Medicine (Baltimore), 2015)
Paroxysmal nocturnal hemoglobinuria (PNH) is a rare acquired disorder of hematopoietic stem cells characterized by hemolytic anemia, marrow failure, and a high incidence of life-threatening venous thrombosis. Cerebral venous system is the second most frequent location of thrombosis after hepatic veins. However, data about PNH-related cerebral venous thrombosis (CVT) are very scarce because of the rarity of both the disorders. We report a French study about PNH patients with CVT. Patients were recruited retrospectively, from the Société Française d’Hématologie (SFH) registry of 465 patients with PNH; the Lariboisière registry of 399 patients with CVT; and a direct contact with 26 French Hematology Units. We review cases reported since 1938 in the English and French language literature. We then compared patients of our series with cases from the literature, with non-PNH-related CVT cases from Lariboisière registry, and with PNH patients without CVT from SFH registry. Fifteen patients were included between 1990 and 2012. Most patients were women (12/15) and half of them presented associated hormonal venous thrombosis risk factors. Three patients had concomitant hepatic vein thrombosis. CVT was the first manifestation of PNH in 4 patients. No major difference in CVT characteristics was found compared with non-PNH-related CVT cases, except for a younger age at diagnosis in PNH patients (P < 0.001). All patients were treated with anticoagulation therapy. One death occurred in acute stage. All surviving patients were independent 1 year after. Median survival time was 9 years. Recurrent thrombosis rate was 50% at 6 years, occurring in patients that did not have bone marrow transplantation or eculizumab therapy. Cases of death were mainly related to hepatic vein thrombosis. Prognosis of CVT was good in our series. However, these patients have a poor long-term prognosis due to PNH disease by itself. PNH treatment should be proposed as soon as possible to avoid recurrent thrombosis. Besides, inaugural CVT events encourage investigating PNH in case of cytopenia, hemolysis, abdominal veins thrombosis, or aplastic anemia history associated with the neurological complication.